2014
DOI: 10.1055/s-0034-1367014
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Parkinsonism and Psychosis with Mirtazapine: A Case Report

Abstract: Therapeutic effects of medication with strong antagonism for 5HT-2 A and 5HT-2C, like mirtazapine, mianserine, trazodone and nefazodone, in Parkinson-related diseases should be subject for further research. Serotonin might be associated with psychosis in Parkinson-related disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Several adrenergic and serotonergic agonists are garnering attention for reducing impulsivity in laboratory rats and humans [5052], additional experimentation with the current model using receptor-selective compounds will be particularly informative. Nonetheless, given the clinical reports showing the efficacy and tolerability of mirtazapine for treating psychiatric disorders in PD patients [2530], our results indicate that further investigations into the utility of mirtazapine for treating PPX-induced ICDs are warranted.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several adrenergic and serotonergic agonists are garnering attention for reducing impulsivity in laboratory rats and humans [5052], additional experimentation with the current model using receptor-selective compounds will be particularly informative. Nonetheless, given the clinical reports showing the efficacy and tolerability of mirtazapine for treating psychiatric disorders in PD patients [2530], our results indicate that further investigations into the utility of mirtazapine for treating PPX-induced ICDs are warranted.…”
Section: Discussionmentioning
confidence: 90%
“…Mirtazapine, an atypical antidepressant, reduces behaviors associated with substance use disorders in rats [1822] and humans [23,24]. Moreover, mirtazapine has been used to treat anxiety, depression, and psychosis in PD patients, and is well-tolerated by PD patients on dopamine agonist therapy with little to no effect on the motor benefits afforded by the agonist [2530]. This latter feature likely reflects the lack of mirtazapine binding to dopaminergic receptors [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Although, occasionally, atypical antipsychotics other than clozapine and quetiapine are still being used, the evidence for lack of efficacy and risk of motor worsening has been confirmed further . A single case report by Godschalx‐Dekker and Siegers using the 5HT‐2 A and 5HT‐2C antagonist, mirtazapine, claimed reduction of psychosis in PD without concomitant depression, but there are no trials . Electroconvulsive therapy (ECT) has not been studied in controlled trials, but a recent case series reported improvement in patients with PD and severe psychosis who did not respond to pharmacological treatments .…”
Section: New Treatments and Discoveriesmentioning
confidence: 99%
“…Mirtazapine (30 mg p.o. hs) was also effective at reducing visual hallucinations in a 67-year-old man with PD previously treated without success with clozapine, quetiapine, and rivastigmine [529]. Similarly, mirtazapine (15 mg p.o.…”
Section: Net Inhibitorsmentioning
confidence: 99%